Corps étrangers dans le Journal de voyage de Montaigne - Anne Duprat (Viatica)
The Journal de voyage written by Montaigne in the 16th century is presented as a simple report of alternating experiences following certain events and the physical condition of the traveller, which contrasts strikingly with the writing of the Essais, which exemplifies continuous inner movement. Indeed, the Journal de voyage is presented as a collection of anecdotes and experiences recounting the effects of a displaced body, without drawing any particular meaning from this. Yet this lack of both reflection and judgment does not prevent the reader from approaching the story from historical, philosophical or literary perspectives.